American foreign policy & the Muslim world - Hossain, Ishtiaq (Al-Zaytouna Centre for Studies and Consulations, 2009)
This book takes an academic, well-documented and comprehensive approach in its analysis. With contributions based in Lebanon, Malaysia, the U.A.E., the U.K. and the U.S.A., the primary objective of this book is to explain the domestic setting of American foreign policy-making and analyse its impact on issues that are considered vital to the Muslim world.